Standardization of time of softwood grafting in mahua (Bassia latifolia) and khirni (Manilkara hexandra) under semi-arid environment of western India - SINGH, SANJAY; SINGH, A K (The Indian Journal of Agricultural Sciences, 2015)
The experiment was conducted during consecutive years of 2005-06 and 2006-07 at Central Horticultural Experiment Station (Central Institute for Arid Horticulture-ICAR), Vejalpur (Godhra), Panchmahal, Gujarat to standardize time of softwood grafting in mahua (Bassia latifolia Roxb.) and khirni (Manilkara hexandra (Roxb.) Dub.) under semi-arid environment of western India. Softwood grafting was carried out at monthly interval commencing from July to June during both the years. Sprouting was found to be the earliest in March (26 days in mahua and 27.4 days in khirni). Maximum time for bud sprouting was taken in the month of September (34.00 days) and November (33.50 days) in mahua and khirni respectively. The highest percentage of graft success was also noted in March, i.e. 70.00 % in mahua and 76.66 % in khirni, it was closely followed by July, August and June. Least percentage of success was noted in the month of September and November in mahua and khirni respectively. Length of sprout was also recorded highest in March after 180 days after grafting in both the crops (28 cm in mahua and 22 cm in khirni). Similar trend was recorded in respect of number and diameter of sprouts. Softwood grafted plants of mahua had higher number of leaves than khirni grafts, whereas it was found to be highest in the month of March in both the crops. Irrespective of scion and rootstock, the maximum accumulation of nitrogen and carbohydrate content was recorded in March, while it was found in lower concentration during December, January and February. Soft wood grafting in mahua may be followed during March, April and July, while March, July and August may be the appropriate time for grafting of khirni under semi-arid environment of western India.